The Role of the Church in Maintaining the Integrity of Faith Amidst Changing Morality in the Digital Era - Immanuela Immanuela (International Journal of Christian Education and Philosophical Inquiry, 2024)
The Role of the Church in Maintaining Faith Integrity Amid Moral Changes Caused by the Digital Era. The core issues in this research include the moral challenges faced by society due to technology, the impact of social media on religious values, and the need to educate congregants in confronting new moral complexities. The aim of this study is to identify strategies that the Church can implement to strengthen the faith of its members and to analyze how these approaches can remain relevant in today’s digital context. The research method employed consists of literature review and interviews with church leaders and congregants to gain deep insights into their experiences and the challenges they face. The state of the art from this research indicates that many churches have begun to adapt technology, but have not fully integrated moral teachings within the digital context. The novelty of this study lies in its holistic approach that combines theology, technology, and social psychology in strategies for maintaining faith integrity. The findings suggest that the Church can act as an agent of change by utilizing digital platforms for education and communication, as well as creating communities that uphold faith values in the face of new moral challenges. This research is expected to provide guidance for the Church in addressing the challenges of the digital era and strengthening its role in the spiritual life of the congregation.